Pemodelan Multivariate Time Series dengan Vector Autoregressive Integrated Moving Average (VARIMA) - Azalia Az-Zahra Nugroho; Suwanda (Jurnal Riset Statistika, 2022)
Abstract. VARIMA (Vector Autoregressive Integrated Moving Average) is a multivariate time series model that explains the linkages between observations on a particular variable at a particular time with the observation of the variable itself at previous times and its linkages with observations on other variables at previous times. Exports are a source of foreign exchange that is needed by the state, while with imports, the country can fulfill its needs that are not owned or produced domestically, and the costs incurred for goods and services become cheaper. Non-oil and gas are the largest contributors to commodities in the value of imports and exports. In this study, multivariate time series data analysis was carried out to estimate the value of non-oil and gas imports and exports in West Java using the VARIMA method. Based on data on non-oil and gas imports and exports in West Java in January 2013–April 2022, the forecasting model obtained and the appropriate is VARIMA (2,1,1). From the model, it can be seen that the value of exports is influenced by the value of imports, and the highest results of import forecasting and non-oil and gas exports will occur in June 2022, and the lowest will occur in May 2022. Abstrak. VARIMA (Vector Autoregressive Integrated Moving Average) adalah salah satu model time series multivariat yang menjelaskan keterkaitan antar pengamatan pada variabel tertentu pada suatu waktu dengan pengamatan variabel itu sendiri pada waktu-waktu sebelumnya, dan keterkaitannya dengan pengamatan pada variabel lain pada waktu sebelumnya. Ekspor merupakan sumber devisa yang sangat dibutuhkan oleh negara, sedangkan dengan adanya impor maka negara dapat memenuhi kebutuhan yang tidak dimiliki atau diproduksi di dalam negeri dan biaya yang dikeluarkan untuk barang dan jasa menjadi lebih murah. Non migas merupakan penyumbang komoditi terbesar pada nilai impor dan ekspor. Dalam penelitian ini dilakukan analisis data time series multivariat untuk meramalkan nilai impor dan ekspor non migas di Jawa Barat dengan menggunakan metode VARIMA. Berdasarkan data impor dan ekspor non migas di Jawa Barat pada Januari 2013-April 2022 diperoleh model peramalan yang didapatkan dan sesuai adalah VARIMA (2,1,1). Dari model dapat diketahui bahwa nilai ekspor dipengaruhi oleh nilai impor dan dari hasil peramalan impor dan eskpor non migas tertinggi akan terjadi pada bulan Juni 2022 dan terendah akan terjadi pada bulan Mei 2022.